2014
DOI: 10.1039/c4ra08791g
|View full text |Cite
|
Sign up to set email alerts
|

Green silver nanoparticles: enhanced antimicrobial and antibiofilm activity with effects on DNA replication and cell cytotoxicity

Abstract: Synthesis of green and biocompatible silver nanoparticles with high anti-microbial and anti-biofilm activities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(20 citation statements)
references
References 52 publications
(48 reference statements)
3
17
0
Order By: Relevance
“…6 value indicates that the green synthesized silver nanoparticles using the leaf extract of guava can inhibit the growth of P. aeruginosa MTCC 741 strain at the concentration of 10 -6 (M). This study is tuned with earlier reported studies: antibacterial activity of Ag nanoparticles on fish pathogen and other microbes (Gupta et al 2014;Velmurugan et al 2014, Mahanty et al 2013. Several mechanisms regarding antimicrobial activity of Ag nanoparticles have been proposed.…”
Section: Resultsmentioning
confidence: 93%
“…6 value indicates that the green synthesized silver nanoparticles using the leaf extract of guava can inhibit the growth of P. aeruginosa MTCC 741 strain at the concentration of 10 -6 (M). This study is tuned with earlier reported studies: antibacterial activity of Ag nanoparticles on fish pathogen and other microbes (Gupta et al 2014;Velmurugan et al 2014, Mahanty et al 2013. Several mechanisms regarding antimicrobial activity of Ag nanoparticles have been proposed.…”
Section: Resultsmentioning
confidence: 93%
“…The MIC value indicates that the green synthesized silver nanoparticles using the leaf extract of vasaka can inhibit the growth of P. aeruginosa MTCC 741 strain at the concentration of 10 -5 (M). This study is tuned with earlier reported studies: anti bacterial activity of Ag nanoparticles on fish pathogen and other microbes [3][4][5].…”
Section: Uv-visible Spectroscopymentioning
confidence: 86%
“…It is revealed that bacteria within biofilm are responsible for more than 80 % infectious diseases as well as more resistance to antibiotics [1]. In recent years, due to unique physical and chemical properties of nanoparticles, its uses to disrupt biofilm of bacteria are revolutionary steps in antimicrobial research [2][3][4][5][6][7][8][9][10][11][12][13]. The uses of silver and silver compounds are very well known from ancient time in case of dental work, catheters and burn wounds etc.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mohanpuria et al [11] have reviewed the synthesis of silver nanoparticles using plants. Gupta et al [12] synthesized silver nanoparticles (AgNPs) using the methanolic extract of Syzygium cumini leaf. The prepared nanoparticles inhibited biofilm formation in a wide range of AgNP concentrations.…”
Section: Introductionmentioning
confidence: 99%